A randomized placebo-controlled study on the effects of lutein and zeaxanthin on visual processing speed in young healthy subjects - Bovier, Emily R.; Hammond, Billy R. (Archives of biochemistry and biophysics, 2015)
Speed of processing is a particularly important characteristic of the visual system. Often a behavioral reaction to a visual stimulus must be faster than the conscious perception of that stimulus, as is the case with many sports (e.g., baseball). Visual psychophysics provides a relatively simple and precise means of measuring visual processing speed called the temporal contrast sensitivity function (tCSF). Past study has shown that macular pigment (a collection of xanthophylls, lutein (L), meso-zeaxanthin (MZ) and zeaxanthin (Z), found in the retina) optical density (MPOD) is positively correlated with the tCSF. In this study, we found similar correlations when testing 102 young healthy subjects. As a follow-up, we randomized 69 subjects to receive a placebo (n=15) or one of two L and Z supplements (n=54). MPOD and tCSF were measured psychophysically at baseline and 4months. Neither MPOD nor tCSF changed for the placebo condition, but both improved significantly as a result of supplementation. These results show that an intervention with L and Z can increase processing speed even in young healthy subjects.